Budgeting Efficiency in the Education System: Measuring the Effectiveness of Public and Private Schools - Yulia Fithriany Rahmah (STAI Hubbulwathan Duri, 2023)
This article examines the efficiency of the education system and measures the effectiveness of public and private senior high schools in the city of Bandung. The samples for this study are 20 high schools in Bandung comprising 10 private schools and 10 public schools. A quantitative approach was utilized as the research design. The analytical tools used are multiple linear regression and Data Envelopment Analysis (DEA). The results showed that private high schools were more efficient than public high schools in Bandung with an average efficiency rate of 91.49%. The achievements of high school students in the city of Bandung are influenced by the number of teachers, number of staff, number of students, school expenses, and graduate teachers, while the teacher's teaching experience does not affect student achievement. Our findings show that private schools are more efficient than public schools. Meanwhile, the amount of the cost of attending private schools is higher, and they tend to serve a smaller, more affluent population. These results highlight the need for policymakers to consider the trade-off between efficiency and equity when making educational funding and resource allocation decisions.